Why does Colombia export security expertise? Security cooperation between status and bureaucracy - Eijking, J (Routledge, 2022)
With funding from third parties such as the United States and Canada, Colombia provides police and military training to Central America’s Northern Triangle. This is puzzling for three reasons: it does little to improve Colombia’s security; the Northern Triangle does not directly affect Colombia’s national security; and Colombia partially pays for it, while it continues to face domestic conflict. Based on document analysis and original interviews with practitioners and advisors, this text argues that status motives de-incentivize impact evaluation; bureaucratic interests render civil oversight difficult; and expert status validates past behaviour and so claims an uncontroversial role for the security sector. This work proposes an interactive effect between status and bureaucracy: status is the state-level motive for a new Colombia that exports security know-how; bureaucratic interests of the security sector explain the shape implementation takes on the ground. A dual function of expertise (as marker of status and as bureaucratic attribute) highlights why Colombia pursues security cooperation now, the way it does. This explanation fares better than neo-utilitarian, neorealist, or neo-Gramscian accounts and provides a useful lens through which to understand the circulation of policy knowledge. It suggests that states can aspire to expert status, and it shows how a former ‘student’ has become a ‘teacher’ in the global market for expertise.